2003
DOI: 10.1093/jn/133.9.2868
|View full text |Cite
|
Sign up to set email alerts
|

Age and Disability Affect Dietary Intake

Abstract: The purpose of the study was to provide information on dietary intake in the InCHIANTI study population, a representative sample (n = 1453) of persons living in two towns of Tuscany (Italy), including a large number of old and very old individuals (79.5% >65 y old). We also investigated whether difficulties in nutrition-related activities were associated with inadequate intake of selected nutrients. The percentage of persons with an inadequate intake of nutrients according to Italian Recommended Nutrients Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 23 publications
6
64
1
3
Order By: Relevance
“…The second limitation is that the population studied is mostly composed of people in advanced age. Thus, taking into account differences in dietary intake that occur with aging [15], these results cannot be automatically extended to younger subjects. The third limitation is represented by the cross-sectional nature of the analysis; a prospective survey on modifications of dietary habits after the diagnosis of diabetes could have been more informative.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is that the population studied is mostly composed of people in advanced age. Thus, taking into account differences in dietary intake that occur with aging [15], these results cannot be automatically extended to younger subjects. The third limitation is represented by the cross-sectional nature of the analysis; a prospective survey on modifications of dietary habits after the diagnosis of diabetes could have been more informative.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have clearly demonstrated that self-perceived chewing ability is very important for the maintenance of good dietary habits in the elderly (Sheiham et al, 1999;Osterberg et al, 2002;Bartali et al, 2003). Furthermore, Gordon et al (1985) suggest that the presence of self-perceived chewing problems often is an indicator of altered food selection patterns in these older individuals, and that this may be a more reliable indicator than the quality of the dentition itself.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for energy intake, also a low intake of protein, vitamin D, E, C, folate and a low intake of more than 3 nutrients at the same time, were significantly related to frailty. In the same study, an inadequate intake of energy was related to functional nutrition related problems like difficulties with chewing, self-feeding, shopping, carrying a shopping bag or cooking [8].…”
Section: Introductionmentioning
confidence: 89%